ANALYSIS OF NURSING CARE WITH THE APPLICATION OF THERMOTHERAPY TO OVERCOME PAIN ACUTE PROBLEMS AMONG ACUTE CORONARY SYNDROME PATIENTS AT ICU RSI JEMURSARI SURABAYA - Handhayani, Riris Dwi; Umamah, Farida; Kamariyah, Nurul; Damawiyah, Siti (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Acute Coronary Syndrome (SKA) includes a heart emergency disease with clinical manifestations in the form of feelings of discomfort or chest pain. Objective: The purpose of this study was to analyze the application of thermotherapy in acute coronary syndrome patients to overcome acute pain problems in ICU RSI Surabaya Jemursari. Methods: This research uses a descriptive method of case studies. The subjects used were 1 patient with acute coronary syndrome who had acute pain nursing problems. Thermotherapy is given for 3 days every 15-20 minutes repeated twice a day or every 12 hours. Data were collected by direct interviews with patients and families, observation and physical examination. Data collection methods include assessment, diagnosis, intervention, implementation and evaluation. Result: After nursing care for 3 days with the application of thermotherapy, namely placing a compress bag containing warm water with a temperature of 50 ° C wrapped with a cloth to be attached to the back / posterior, and attaching a warm compress cloth to the patient's chest area for 15-20 minutes repeated 2x or per 12 hours making the pain felt by the patient can decrease until it does not feel evidenced by complaints of decreased pain, Grimacing decreases, restlessness decreases, difficulty sleeping decreases, pulse frequency improves, breathing patterns improve. Conclusion: The application of thermotherapy has proven effective in reducing acute pain in the chest in patients with acute coronary syndrome. For health services, this research can be applied in nursing services professionally in improving nursing care comprehensively, making thermotherapy one of the non-pharmacological therapies to overcome acute pain.